Bacterial dynamics and chemical changes during the spontaneous production of the fermented porridge (Calugi) from cassava and corn - Miguel, Maria Gabriela da Cruz Pedrozo (2014)
A traditional fermented porridge made from maize, cassava and rice, named calugi, was microbiologically and chemically analyzed. Our results show that aerobic mesophilic bacteria reached values of approximately 7 log CFU ml-1 and were the predominant group; acetic acid bacteria were also observed at the onset of fermentation (3.82 log CFU ml-1). The population of lactic acid bacteria was 3.7 log CFU ml-1 and remained constant throughout the fermentation. The denaturing gradient gel electrophoresis (DGGE) bands were identified as Corynebacterium variabile, Lactobacillus paracasei, L. plantarum, L. casei, Bacillus spp. (Bacillus cereus group), B. subtilis, Streptomyces sp., Enterobacter cloacae, Streptococcus parasanguis, Streptococcus salivarius, Weissella cibaria and Weissella confusa, in addition to uncultivable bacteria. The most abundant carbohydrate in the substrate was maltose (38 g L-1 at the beginning of fermentation). Acetic and lactic acids were the principal acids found by high performance liquid chromatography (HPLC) (0.66 g L-1 and 3.54 g L-1, respectively). Twenty-one (21) minor compounds were identified by gas chromatography during the fermentation process. The compounds present at the highest concentrations were furfuryl alcohol, nonanoic acid, decanoic acid and 1,1-dietoxyethane. These appeared to be related to the flavor of the calugi.